2018
DOI: 10.1029/2018ms001484
|View full text |Cite
|
Sign up to set email alerts
|

The Life Cycle and Net Radiative Effect of Tropical Anvil Clouds

Abstract: We explore the importance of the life cycle of detrained tropical anvil clouds in producing a weak net cloud radiative effect (NCRE) by tropical convective systems. We simulate a horizontally homogeneous elevated ice cloud in a 2‐D framework using the System for Atmospheric Modeling cloud‐resolving model. The initially thick cloud produces a negative NCRE, which is later canceled by a positive NCRE as the cloud thins and rises. Turning off interactive cloud radiation reveals that cloud radiative heating and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 58 publications
9
32
1
Order By: Relevance
“…Simulations without the effects of ACRE could not achieve a near cancelation of the SW and LW CRE as observed in the deep tropics, leading instead to a strongly negative net CRE. Radiative heating promotes the formation and maintentance of thin anvils, which is similar to the results by Hartmann et al (2018) who used a very simple cloud geometry. We find the horizontal spreading of the cloud to be the key feature influencing the radiative effects integrated over the whole convective life cycle.…”
Section: Drivers Of Anvil Evolutioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Simulations without the effects of ACRE could not achieve a near cancelation of the SW and LW CRE as observed in the deep tropics, leading instead to a strongly negative net CRE. Radiative heating promotes the formation and maintentance of thin anvils, which is similar to the results by Hartmann et al (2018) who used a very simple cloud geometry. We find the horizontal spreading of the cloud to be the key feature influencing the radiative effects integrated over the whole convective life cycle.…”
Section: Drivers Of Anvil Evolutioncontrasting
confidence: 99%
“…Such clouds contain IWP of 5 to 150 g/m 2 and have COD between 1 and 6, and net CRE of about +5 to −25 W/m 2 . The upper tropospheric cloud peak spreads toward higher altitudes when transiting to lower IWP values due to either the in situ formation of new ice clouds or by lofting of anvil remains, as suggested by Hartmann and Berry (2017) and modeled by Hartmann et al (2018). Remarkably, the net CRE shifts from values around −100 W/m 2 for the highest percentiles, toward +15 to +30 W/m 2 for the 40th to 70th percentiles.…”
Section: Observational Datasupporting
confidence: 83%
See 1 more Smart Citation
“…Note that such an alteration is only applied to the radiation calculation. We found that changing RR ei exerts negligible effect on the ice mass and number concentrations, so the proposed enhanced turbulence and cirrus cloud vertical development by in-cloud radiative heating (Hartmann et al, 2018) does not occur in such a large-scale model. The same magnitude of perturbations was applied to RR ei in the radiation scheme.…”
Section: Parameter-perturbation Experiments Designmentioning
confidence: 77%
“…The vertical profile of cloud water specific humidity is more bottom heavy than that of cloud fraction, with a more obvious peak near the melting level. In general, the LES produce little cloud ice in the upper troposphere in deep convection regions, which may be related to the relatively simple microphysics scheme and the lack of cloud-radiation interactions (Hartmann et al, 2018) in this study.…”
Section: Les Initial Conditionmentioning
confidence: 80%